Morchella esculenta (L.) Pers. extract exhibits selective anticancer activity by modulating ATF3/Keap1/Nrf2/HO-1/NQO1 signaling and suppressing cell migration - Ozek, Dilan Askin; Ozgen, Ridvan; Yuce, Hande; Berberoglu, Yasemin; Gurhan, Ismet; Arabaci, Turan; Unuvar, Songul (Elsevier, 2026)
Morchella esculenta (L.) Pers. is traditionally consumed as a functional food with reported antioxidant and health-promoting properties. However, its anticancer activity and underlying molecular mechanisms remain insufficiently elucidated. This study aimed to characterize the bioactive profile of M. esculenta and to explore its possible antioxidant, cytotoxic, and anti-migration effects on PC3, Hep3B, and HCT116 cancer cell lines, with an emphasis on apoptosis and oxidative stress-related pathways. Phenolic compounds and amino acids were analyzed by LC-MS/MS, and fatty acids by GC-FID. Antioxidant activity was assessed using DPPH and ABTS assays. Cytotoxicity was evaluated by MTS assay, migration by wound healing, and gene expression (ATF3, Keap1, Nrf2, HO-1, NQO1, Bax, Bcl-2, Cas-3, Cas-9) by RT-qPCR. The extract showed a diverse bioactive composition, predominantly containing fumaric and quinic acids, as well as major fatty acids such as linoleic and oleic acids. It induced dose-and time-dependent reductions in cell viability and was associated with inhibition of cell migration, particularly in PC3 and Hep3B cells. Apoptosis-related changes were observed, including increased expression of Bax, Cas-3, and Cas-9, together with decreased Bcl-2 levels. In addition, modulation of genes related to the ATF3/Keap1/Nrf2/HO-1/NQO1 axis suggests a possible involvement of oxidative stress-related mechanisms. These effects were more pronounced in cancer cell lines compared to L929 cells, which showed relatively lower sensitivity. Overall, the findings indicate that M. esculenta may exert bioactivity in cancer cell models through effects on proliferation, migration, and apoptosis-related pathways. However, further functional and in vivo studies are required to better clarify the underlying mechanisms and to evaluate its potential biological relevance.
Keywords: Morchella Esculenta; Amino Acid Profile; Fatty Acid Composition; Antioxidant Activity; Cell Viability